2000
DOI: 10.3168/jds.s0022-0302(00)75012-0
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Duodenal Infusions of Palmitic, Stearic, or Oleic Acids on Milk Composition and Physical Properties of Butter

Abstract: Four dairy cows fitted with a duodenal cannula were used in a 4 x 4 Latin square design to investigate the effects of daily duodenal infusion of 500 g of fatty acids (containing mainly C16:0, C18:0, or cis-C18:1) on fecal concentrations of fatty acids, fatty acid profiles of milk fat, and solid fat content of butter. Fecal concentrations of C16:0 and especially of C18:0 were increased by duodenal infusion. Infusion with C16:0 increased the proportion of C16:0 in milk fat and delayed softening of butter when th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
40
2

Year Published

2004
2004
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(55 citation statements)
references
References 26 publications
13
40
2
Order By: Relevance
“…C16:0 was the fatty acid that contributed most to the melting point of the MMF and was the only fatty acid among the relevant fatty acids selected to be positively correlated with the melting point of the MMF. Previous studies have demonstrated that, by increasing C16:0 in milk fat, both melting point and hardness increase . The same behaviour was expected for C14:0 and C18:0, which are quantitatively high; however, in the present study their contribution was not significant.…”
Section: Resultssupporting
confidence: 83%
“…C16:0 was the fatty acid that contributed most to the melting point of the MMF and was the only fatty acid among the relevant fatty acids selected to be positively correlated with the melting point of the MMF. Previous studies have demonstrated that, by increasing C16:0 in milk fat, both melting point and hardness increase . The same behaviour was expected for C14:0 and C18:0, which are quantitatively high; however, in the present study their contribution was not significant.…”
Section: Resultssupporting
confidence: 83%
“…The authors suggested that this low transfer efficiency was related to oxidation of the FA as metabolic fuel rather than export as milk triglycerides. In contrast, a higher FAYR (46.7%), calculated as the additional C16:0 consumed and partitioned to milk relative to control, has been reported when 490 g of palmitic acid was infused in the duodenum (Enjalbert et al, 2000). In our study, increased milk fat yield was accounted for by the increase in total 16-carbon FA in milk.…”
Section: Discussioncontrasting
confidence: 57%
“…Long-chain saturated fat supplements have been used to increase the energy density of diets (Wang et al, 2010) and milk fat yield (Steele and Moore, 1968;Steele, 1969;Wang et al, 2010) in dairy cows and have been reported to increase feed efficiency (Wang et al, 2010;Lock et al, 2013) and milk yield (Steele, 1969;Enjalbert et al, 2000). Moreover, they are considered to be inert in the rumen (Grummer, 1988;Schauff and Clark, 1989), and have little effect on DMI (Allen, 2000) and nutrient digestibility (Grummer, 1988;Schauff and Clark, 1989;Elliott et al, 1996).…”
Section: Introductionmentioning
confidence: 97%
“…In contrast, high-palmitic acid supplements increased milk fat yield in several studies spanning over 4 decades (Steele and Moore, 1968;Enjalbert et al, 2000). Specifically, increasing intake of C16:0 within a range of 1.8 to 5.2% of DMI linearly increased milk fat yield and C16:0 incorporation into milk fat (Mosley et al, 2007) and recent experiments also reported increased milk fat concentration and yield (80 to 100 g/d; Lock et al, 2013;Piantoni et al, 2013).…”
mentioning
confidence: 85%
“…An SFA supplement enriched in palmitic acid has recently garnered interest Piantoni et al, 2013;, as mammary extraction efficiency of palmitic acid is greater than that of stearic acid (Enjalbert et al, 2000). However, the response to enriched palmitic acid supplements also has been vari-able, with increased milk fat yield observed in some, but not all, experiments (see .…”
Section: Introductionmentioning
confidence: 98%